Aggressive and Prosocial Behavior: Community Violence, Cognitive, and Behavioral Predictors Among Urban African American Youth. Issue 3 (11th December 2012) - McMahon, Susan D.; Todd, Nathan R.; Martinez, Andrew; Coker, Crystal; Sheu, Ching-Fan; Washburn, Jason; Shah, Seema
Abstract: We use longitudinal multilevel modeling to test how exposure to community violence and cognitive and behavioral factors contribute to the development of aggressive and prosocial behaviors. Specifically, we examine predictors of self‐, peer‐, and teacher‐reported aggressive and prosocial behavior among 266 urban, African American early adolescents. We examine lagged, within‐person, between‐person, and protective effects across 2 years. In general, results suggest that higher levels of violence exposure and aggressive beliefs are associated with more aggressive and less prosocial peer‐reported behavior, whereas greater self‐efficacy to resolve conflict peacefully is associated with less aggression across reporters and more teacher‐reported prosocial behavior. Greater knowledge and violence prevention skills are associated with fewer aggressive and more prosocial teacher‐reported behaviors. Results also suggest that greater self‐efficacy and lower impulsivity have protective effects for youth reporting higher levels of exposure to community violence, in terms of teacher‐reported aggressive behavior and peer‐reported prosocial behavior. Differences among reporters and models are discussed, as well as implications for intervention.